PENGARUH STRES DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA KARYAWAN CV PUTRA GUNA MAKMUR DI SIDOARJO - Junaedi, Marliana; Subrata, Yuanda Tanu; Koemono, Teman (KINDAI, 2024)
Abstract: This study aims to analyze the effect of work stres and work motivation on employee performance with job satisfaction as the mediation. The subjects of this study were 135 employees of CV Putra Guna Makmur Sidoarjo. Data is processed with SmartPLS 4 through Outer Model and Inner Model (R-Square) testing. The results of this study indicate that job stres has a positive effect on job satisfaction, then work motivation has a positive effect on job satisfaction. Furthermore, job satisfaction has a positive effect on employee performance. Mediation analysis confirmed that the effect of stress and motivation on employee performance is mediated by job satisfaction. These findings highlight the importance of managing job stress and increasing employee motivation to improve overall satisfaction and performance. Furthermore, this study provides a practical contribution for CV Putra Guna Makmur in designing policies that support employee well-being and performance. Keywords: job stress, job motivation, job satisfaction, employee performance